Analisis Risiko Produksi Bawang Merah di Desa Songan B, Kecamatan Kintamani, Kabupaten Bangli - ANJELINA PUTRI; RATNA KOMALA DEWI; I DEWA AYU SRI YUDHARI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Risk Analysis of Red Onion Production in Songan B Village Kintamani District,Bangli Regency Songan B Village is one of the villages that develop onion farming. Songan B villagehas farmer groups spread from the lowland to the highland areas. The problems facedare on the fluctuation of onion productivity which indicates that onion farming facesproduction risk. This study aimed to identify the types of risks and analyze the risk ofonion production. This research used quantitative and qualitative analysis. The resultsshowed that the types of production risks encountered in onion farming in the highlandand lowland areas in the village of Songan B, namely climatic conditions, pest, anddisease attacks. The risk of onion production in the highland areas (KV = 3.09) andlowland areas (KV = 2.46) was relatively high, where the level of risk of onionproduction in the highland areas was greater than that in the lower regions. This is dueto the expected production, variant, and standard deviation of onion productivity in thehighland areas is greater than that in the lower regions. The suggestion that can be givenin this research is that farmers need to recognize the types of production risks faced inorder to anticipate production decline.